2020
DOI: 10.1016/j.celrep.2020.01.093
|View full text |Cite
|
Sign up to set email alerts
|

TIFAB Regulates USP15-Mediated p53 Signaling during Stressed and Malignant Hematopoiesis

Abstract: Graphical Abstract Highlights d TIFAB binds the catalytic domain of USP15 and increases its rate of deubiquitination d TIFAB regulates USP15-dependent signaling in hematopoietic cells d Loss of TIFAB sensitizes HSPCs to p53-dependent stress d TIFAB is overexpressed and functionally relevant in MLLrearranged AML

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 75 publications
2
43
0
Order By: Relevance
“…To gain additional insight into the functional role of TIFAB in del(5q) MDS/AML, a proteomics screen was performed to identify TIFAB-binding proteins. Mass spectrometry analysis confirmed that TIFAB binds endogenous TRAF6 in a human del(5q) AML cell line, but these studies also revealed that TIFAB readily binds the ubiquitin-specific peptidase USP15 [18]. A series of biochemical assays and co-immunoprecipitation experiments confirmed that TIFAB binds USP15, and this appears to be partly dependent on the deubiquitinating (DUB) activity of USP15.…”
Section: Traf-interacting Proteins With Fha Domainsmentioning
confidence: 85%
See 4 more Smart Citations
“…To gain additional insight into the functional role of TIFAB in del(5q) MDS/AML, a proteomics screen was performed to identify TIFAB-binding proteins. Mass spectrometry analysis confirmed that TIFAB binds endogenous TRAF6 in a human del(5q) AML cell line, but these studies also revealed that TIFAB readily binds the ubiquitin-specific peptidase USP15 [18]. A series of biochemical assays and co-immunoprecipitation experiments confirmed that TIFAB binds USP15, and this appears to be partly dependent on the deubiquitinating (DUB) activity of USP15.…”
Section: Traf-interacting Proteins With Fha Domainsmentioning
confidence: 85%
“…Amidst emerging fields uncovering the fascinating connections between immune cell function, chronic inflammation, and malignant conditions, TIFA and TIFAB demand further understanding. Given the fact that TIFA and TIFAB are potential therapeutic targets in AML [18,39], studies elucidating structural information on TIFA and TIFAB should be useful for the development of novel therapeutics against infectious diseases and possibly cancers. These small FHA domain-containing proteins are potent signal transducers with pleiotropic effects, many of which are yet to be discovered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations